Direct observational time and motion study of the daily activities of hospital dispensary pharmacists and technicians. (28th January 2023) - Magee, Katie; Fromont, Molly; Ihle, Eloise; Cheung, Michael; Percival, Mia; Poole, Susan G.; Bell, Chloe; Theobald, Belinda; Dooley, Michael J.; Brown, Catherine
Abstract: Background: Hospital pharmacy dispensaries are busy work environments where staff are involved in a variety of work‐related tasks. The proportion of time spent on daily tasks, task prioritisation, multitasking, and interruptions remains largely unknown. Aim: To examine the tasks performed and proportion of time pharmacists and pharmacy technicians in a hospital pharmacy inpatient dispensary spend on various work‐related activities. Method: Pharmacists and technicians working in the inpatient dispensary of a large metropolitan health service were directly observed by trained researchers. Tasks were recorded using Work Observation Method By Activity Timing (WOMBAT), a validated technique developed for direct observation studies of health professionals. Timed tasks were allocated to domains detailing the task performed, who performed it, who they interacted with, and where the task was performed. Data were analysed descriptively with independence of 95% confidence intervals (CI) demonstrating statistical significance. Results: Twelve pharmacists and 13 technicians were observed for 107.4 h. Tasks that contributed the greatest proportion of time were: the preparation of discharge prescriptions: pharmacists 32.1% (95% CI 29.9–34.3%) and technicians 21.0% (95% CI 18.3–23.7%); inpatient medication supply 22.5% (95% CI 21.5–23.5%) and 49.3% (95% CI 47.3–51.3%) and; inter‐professional communication 13.6% and 14.7% (non‐significant [NS]). Tasks were completed independently 89.6% (pharmacists) and 88.9% (technicians) of the time. Pharmacists and technicians were interrupted 6.7 and 5.1 times per hour (p < 0.05), respectively; 8.6% and 9.5% (NS) of the time was spent undertaking at least two tasks simultaneously. Conclusion: This is the first study to examine task time distribution within a hospital inpatient dispensary. Pharmacists and technicians spend the greatest proportion of time on direct medication dispensing‐related activities. This study demonstrates a high frequency of multitasking and interruptions, both of which are known risks for dispensing errors.